2021
DOI: 10.3389/fped.2021.640857
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Antibiotic De-escalation in Critically Ill Children With Sepsis – A Prospective Analytical Study From a Pediatric ICU

Abstract: Introduction: De-escalation is the key to balance judicious antibiotic usage for life-threatening infections and reducing the emergence of antibiotic resistance caused by antibiotic overuse. Robust evidence is lacking regarding the safety of antibiotic de-escalation in culture negative sepsis.Materials and Methods: Children admitted to the PICU during the first 6 months of 2019 with suspected infection were included. Based on the clinical condition, cultures and septic markers, antibiotics were de-escalated or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
(29 reference statements)
0
9
0
1
Order By: Relevance
“…The results indicate that the antimicrobial step-down therapy features a promising clinical Step-down therapy is an empirical anti-infective regimen with the following two characteristics: (1) a single, broad-spectrum, potent antibiotic is used at the beginning of anti-infective therapy to cover as many germs as possible that may cause the infection; (2) after 48-72 h, the antibiotics are adjusted according to the results of microbiological examination of drug sensitivity to be more targeted. It is a new treatment strategy adopted in recent years for severe bacterial infections [21,22]. The strategy consists of two phases: the first phase is empirical treatment with broadspectrum antibiotics, and the second phase is downgrading to a relatively narrow spectrum of antibiotics, which is the adjustment of relatively narrow-spectrum, targeted antibiotic species according to microbiological examination and drug sensitivity results, to shorten the course of treatment, and to maximize the best possible efficacy of anti-infective treatment [23].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that the antimicrobial step-down therapy features a promising clinical Step-down therapy is an empirical anti-infective regimen with the following two characteristics: (1) a single, broad-spectrum, potent antibiotic is used at the beginning of anti-infective therapy to cover as many germs as possible that may cause the infection; (2) after 48-72 h, the antibiotics are adjusted according to the results of microbiological examination of drug sensitivity to be more targeted. It is a new treatment strategy adopted in recent years for severe bacterial infections [21,22]. The strategy consists of two phases: the first phase is empirical treatment with broadspectrum antibiotics, and the second phase is downgrading to a relatively narrow spectrum of antibiotics, which is the adjustment of relatively narrow-spectrum, targeted antibiotic species according to microbiological examination and drug sensitivity results, to shorten the course of treatment, and to maximize the best possible efficacy of anti-infective treatment [23].…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, the role of laboratory tests is vital to help distinguish patients with bacterial infections, guiding decision-making on whether to start, continue, or discontinue the established treatment (6). On the other hand, when further studies cannot con rm bacterial infection and discontinuation of antibiotic treatment may be indicated, our ndings suggest that discontinuation of antibiotics appears to be a safe strategy even in critically ill children (5).…”
Section: Discussion Andmentioning
confidence: 77%
“…Approximately, three-quarters of the antibiotic therapies are equivocally prescribed for respiratory infections of viral origin (1,2). This unnecessary use of antibiotics contributes signi cantly to increasing bacterial resistance as well as morbidity and mortality (3,4), and rising health care costs (5). Therefore, methods to detect and distinguish early between bacterial or viral infection are important, as the clinical presentation can often be indistinguishable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ying Guo et al [ 26 ] performed a meta-analysis that reported a de-escalation rate of 39.5% for the antibiotics used in adult patients with severe sepsis and this did not have a detrimental impact on mortality. Furthermore, in a recent publication, Battula et al [ 27 ] reported a de-escalation in 59% of the episodes of sepsis admitted to PICUs and concluded that this strategy appears to be safe.…”
Section: Discussionmentioning
confidence: 99%